PROFESIONALISME WARTAWAN POLITIK PADA MEDIA ONLINE DI SULAWESI SELATAN - Jaminah Jaminah; Muliadi Mau; Judhariksawan Judhariksawan; Canggi Araliya Aprianti Ode; Nursyamsi Nursyamsi (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Buton, 2022)
The purpose of this study was to determine the level of professionalism of political journalists in online media. The research approach used is quantitative with descriptive method. This research was conducted in South Sulawesi Province and lasted for four months. The criteria for online media that are the object of this research are: the website can still be accessed, there are political news channels, and there are political news posts during the research period, based on these criteria the total population is 30 online media. In this study, researchers used two kinds of data collection techniques, namely: Primary data collection through questionnaires and observations and secondary data collection through documentation and literature studies. The results of this study indicate that the professionalism of political journalists in online media in South Sulawesi is in the high category as measured by 5 indicators, namely: decent salary aspects, adhering to the Journalistic Code of Ethics, joining professional organizations, dedication, and aspects of mastering journalistic skills. As for the aspects of the professional level of journalists that fall into the high category, namely aspects of education and special training in journalism, aspects of complying with the journalistic code of ethics, joining professional organizations, aspects of dedication, and aspects of journalistic code of ethics skills. Meanwhile, the only aspect that falls into the medium category is the aspect of a decent salary.